O ÊXODO DA MINORIA BRANCA DE ANGOLA Adaptações ao contexto brasileiro - Barreto, Isabel de Souza Lima (Outros Tempos: Pesquisa em Foco - História, 2012)
This paper aims to reflect about the process of adaptation of migrants who arrived in Brazil betweenthe end of 1974 and the year of 1976 because of the decolonization process of Angola. There are those whomigrated with their own resources directly to Brazil, there are those who lived a period in Portugal or in SouthAfrica before settling permanently in Brazil. When they arrived here, some found facilities in the process ofreception and adaptation. These are: relatives who lived in Rio de Janeiro, facilities created by the Braziliangovernment to get visas, assistance by institutions of the Portuguese community, and even assistance byunknown persons. There are, however, who has gone through initial difficulties. To give a bettercomprehension of the arrival of these immigrants, we'll do references to the colonial war and to thedecolonization process.